Sintesis Nanofiber Polianilin menggunakan Polimerisasi Interfasial - Nurrahmi, Sitti; Rani, Sefrilita Risqi Adikaning; Minarti, Minarti (SAINFIS: Jurnal Sains Fisika, 2021)
Has done research on synthesis polyaniline nanofiber with variation concentration of dopan hydrochloric acid (HCl that variated the concentration 0,6 M, 1,8 M, and 3 M, in two phase system which are organic phase (solution monomers aniline and solution toluene) and liquid phase ( solution APS and HCl), made ± 15 hours, to obtained polymerization complete ( interfasial ). Scanning Electron Microscopy (SEM) shows that the greater concentration of acid used in the synthesis, obtained diameters of polyaniline nanofiber smaller and the fiber formed has also become clear and uniform. Using HCl 0,6 M obtained diameters of nanofiber (65,2 ± 0,6) nm, 1,8 M obtained diameters (56,1 ± 0,5) nm, and 3 M obtained diameters (45,7 ± 0,4) nm. When obtained the clear and uniform nanofiber, it can be used for the application of censorship and the corrosion.